Planificación del mantenimiento preventivo para los neumáticos de la flota de camiones de la Empresa de Transportes Rodrigo Carranza - Dávila Cipriano, Ronald Jesús (2019)
In the present work of investigation, the planning of the preventive maintenance for the tires of the fleet of trucks of the transport company Rodrigo Carranza was carried out. With the objective of increasing the availability of the trucks to carry out the various operations that the company's customers require. In this thesis, the work stages were Identification of the type of work operation of the fleet, selection of the right type of tire, verifying its status, identifying the control indicators and maintenance programming. By applying this proposal, it was possible to increase availability by 3%. It was also possible to establish indicators to ensure adequate maintenance management, reducing the operating cost and increasing tire performance. Finally, maintenance strategies and training were established for all personnel involved with the tires.